Non-program Classification of Expenses of the Program Budget - Anatoly Yakovlevich Zaporozhan (Управленческое консультирование)
The article is devoted to consideration of problems of formation in Russia of program budgeting in which development the negative tendency of absolutization of program financing when the budgetary expenses «squeeze» into program expenses was outlined, and budgets of the country, regions, municipalities can turn into set of budgets, respectively, the state, regional and municipal programs. The idea of the program budget can be as a result discredited. Not to allow it, it is necessary to divide accurately program and operating costs, to differentiate the budgetary expenses on financing of the current activity and on financing of programs.